ADMINISTRASI PELAYANAN PENERBITAN SURAT IZIN PENANGKAPAN IKAN (SIPI) PADA DINAS KELAUTAN DAN PERIKANAN PROVINSI SULAWESI UTARA - DJUNNU, HARISMAN; POSUMAH, JOHNNY HANNY; PALAR, NOVIE (Sam Ratulangi University, 2019)
This study is about the administration of the service of issuing permits for fishing in the marine and fisheriesservice of North Sulawesi Province. Public service regulations that are still scattered in the number ofregulation that are sectoral, making public services in Indonesia are in a conditional that is not yetmanageable. In other words the community has not received the excellent service that was their hope. Inorder to know the quality of service that is felt significantly by consumers, there are indicators of consumersatisfaction measures that lie in the five dimensions of service quality. 1). Tangibles : Service quality in thefrom of physical facilities, offices, computerized administration, waiting room, information places. 2).Reliability : The ability and reliability to provide trusted service. 3). Responsivess : The ability to help andprovide services quickly and accurately, as well as being responsive to consumer desires. 4). Assurance :The ability and friendliness as well as the courtesy of employees in convincing consumer trust. 5). Emphaty: Firm but attentive attitude of employees toward consumers. In this study the authors used a qualitativeapproach with descriptive analysis techniques, in this study primary data were obtained from interview andcould also be from the result of questionnaires, while secondary data were obtained from documents fromeither the relevant agencies or other relevant agencies. The result have not been able to optimally meet theneeds of the service user community. Researchers provide advice on this is about these five aspects : 1).Tangibles aspects : updating both the quality and quantity of facilities or infrastructure available at themaritime and fisheries service office in North Sulawesi Province. 2). Reliability aspects : Strive for theability and reliability of officers to the provide services by attending training, both internal and external. 3).Responsiveness aspects : Every service officer or apparatus at the North Sulawesi Province’s Office ofmaritime affairs and fisheries must try to increase understanding quickly and precisely on what is theproblem of service needs desired by the community. 4). Assurance aspects : each service officer mustimprove attitudes towards all citizens who need service. 5). Emphaty aspects : every officer is required tohave firmness in carrying out their duties and responsibilities.Keywords : Administration, Service, Fishing license